2018
DOI: 10.1016/j.ijsu.2018.05.738
|View full text |Cite
|
Sign up to set email alerts
|

Technique and surgical outcomes of mesenterization and intra-operative neural monitoring to reduce recurrent laryngeal nerve paralysis after thoracoscopic esophagectomy: A cohort study

Abstract: The combination of IONM and the concept of the mesoesophagus have substantial advantages in allowing accurate and safe mediastinal lymphadenectomy during prone esophagectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 21 publications
0
29
1
Order By: Relevance
“…Unfortunately, the authors did not mention how the intraoperative ventilation was performed [12]. In addition, Kobayashi and colleagues demonstrated that IONM can significantly reduce RLN paralysis in esophageal cancer surgery and is associated with shorter postoperative hospital stay because of a lower rate of postoperative complications [13]. The most common method for IONM is the evoked laryngeal electromyography, which implies the stimulation of the recurrent laryngeal or the vagal nerve and consecutive recording of the EMG signal at the laryngeal muscles via laryngeal needle electromyography, laryngeal surface electrodes or special EMG ETT systems [10].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the authors did not mention how the intraoperative ventilation was performed [12]. In addition, Kobayashi and colleagues demonstrated that IONM can significantly reduce RLN paralysis in esophageal cancer surgery and is associated with shorter postoperative hospital stay because of a lower rate of postoperative complications [13]. The most common method for IONM is the evoked laryngeal electromyography, which implies the stimulation of the recurrent laryngeal or the vagal nerve and consecutive recording of the EMG signal at the laryngeal muscles via laryngeal needle electromyography, laryngeal surface electrodes or special EMG ETT systems [10].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, thyroid redo-surgery leads to higher rates of [24], 4R lymph node station 4R according to [24], 7 lymph node station 7 according to [24] [30]. In esophageal surgery, the use of intraoperative nerve monitoring was shown to be associated with a reduction in the postoperative VCP rate, e.g., from 9.8 to 0% (p = 0.029) in open surgery and 32.1 to 9.7% (p = 0.03) in minimally invasive esophagectomy [6,7]. In 2012, Zhong et al reported an algorithm for IONM in open thoracic esophagectomy.…”
Section: Discussionmentioning
confidence: 95%
“…In open thoracic esophagectomy with extended 2-field lymphadenectomy, the use of RLN monitoring was described as a useful method, which leads to a reduction of cases with postoperative vocal cord paresis [3,6]. In minimally invasive (thoracoscopic) esophagectomy, the use of IONM for RLN detection before visual contact ("mapping") was proven to be associated with a reduction of the postoperative vocal cord paresis rate, when compared with esophagectomy without IONM support [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that IONM could help the surgeon to identify and preserve the RLN before energy devices touch it. 72,73 Meanwhile, IONM is also very helpful in avoiding bilateral RLN palsy during surgery. The LNs along the right RLN are usually removed first in MIE; once IONM indicates an injury of the right RLN in the lymphadenectomy, the dissection of the left RLN nodes should be extremely careful or has to be abandoned to avoid catastrophic bilateral RLNs palsy.…”
Section: Rln Protection In Miementioning
confidence: 99%